Microcalcification Discrimination in Mammography Using Deep Convolutional Neural Network: Towards Rapid and Early Breast Cancer Diagnosis - Yew Sum Leong; Khairunnisa Hasikin; Khin Wee Lai; Norita Mohd Zain; Muhammad Mokhzaini Azizan (FRONTIERS, 2024)
Indexed by WOS/ERA